Pal̲antamiḻilamaippiyal maṟṟum kur̲iyiyal āyvukaḷ - Tamiḻavaṉ (Ulakat Tamil̲ārāycci Niṟuvaṉam, 2009)
Study on semiotics in ancient Tamil philology and literature
Includes bibliographical references (p. 135-136). - In Tamil-Schr
Keywords: Tamil philology; Semiotics and literature